Analisis Nilai Ekspor Impor Menurut Standard International Trade Classification (SITC) di Provinsi Sumatera Barat Menggunakan Analisis Profil - Tia Istiramadhani; Helma Helma (Journal of Mathematics UNP, 2022)
Export is the activity of selling goods and services produced domestically to foreign countries. Meanwhile, import is the activity of purchasing goods and services made abroad into the country. If the value of exports and imports experiences instability, the country's economy will also experience instability which will have an impact on the country's income. For this reason, it is necessary to describe the comparison of the value of exports and imports in the province of West Sumatra according to the Standard International Trade Classification (SITC) using profile analysis. This research aims to determine the class of goods according to the Standard International Trade Classification (SITC) which is optimal using profile analysis. In the profile analysis, a comparison of the average value of exports and imports is carried out using the parallelism test, the overlap test and the level test and continued testing for each variable. The results of the tests that have been carried out are that the item code 4 (vegetable and animal oil/fat) has developed well.